2012
DOI: 10.2478/s11686-012-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA)

Abstract: The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 97 publications
2
9
0
4
Order By: Relevance
“…Then, our recent studies further revealed the heterogeneity of Chinese Leishmania isolates since several species, including L. donovani complex, L. gerbilli, L. tropica, and L. turanica, have been identified (Cao et al 2011;Yang et al 2010Yang et al , 2013. Moreover, a novel and undescribed Leishmania species may exist in China (Cao et al 2011;Guan et al 2012;Sun et al 2012). Nevertheless, the phylogenetic relationships and taxonomy of Chinese Leishmania have not been completely clarified, especially identification within species complex.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Then, our recent studies further revealed the heterogeneity of Chinese Leishmania isolates since several species, including L. donovani complex, L. gerbilli, L. tropica, and L. turanica, have been identified (Cao et al 2011;Yang et al 2010Yang et al , 2013. Moreover, a novel and undescribed Leishmania species may exist in China (Cao et al 2011;Guan et al 2012;Sun et al 2012). Nevertheless, the phylogenetic relationships and taxonomy of Chinese Leishmania have not been completely clarified, especially identification within species complex.…”
Section: Introductionmentioning
confidence: 94%
“…In our previous studies, traditional viewpoints on taxonomy and cladistics hypotheses of Chinese Leishmania isolates have been challenged based on different molecular markers (Cao et al 2011;Guan et al 2012;Yang et al 2010). More effective markers are still needed to clarify the species status and phylogeny of Leishmania in China.…”
Section: Introductionmentioning
confidence: 98%
“…However, most of these studies were aimed to analyse isolates/strains from one particular geographic region, and only a few authors have investigated phylogenetic relationships within the entire genus (Croan and Ellis, 1996;Croan et al, 1997;Dávila and Momen 2000;Berzunza-Cruz et al, 2002;Luyo-Acero et al, 2004;Zelazny et al, 2005; Spanakos et al, 2008;Villinski et al, 2008;Asato et al, 2009;Guan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The use of molecular sequence techniques is providing a large amount of additional data for phylogenetic analyses, but in spite of this, evolutionary relationships remain to be solved (Hughes and Piontkivska, 2003). Different molecular markers have been used for phylogenetic studies in Leishmania: the internal transcribed spacer (ITS) 1 and 2 of the ribosomal DNA array (Cupolillo et al, 1995;Dávila and Momen, 2000;Berzunza-Cruz et al, 2002;Orlando et al, 2002;Kuhls et al, 2005;Spanakos et al, 2008;Sukmee et al, 2008;Villinski et al, 2008), a repetitive DNA sequence (Piarroux et al, 1995), the gene for DNA polymerase α catalytic subunit (POLA, Croan et al, 1997), the gene encoding the largest subunit of RNA polymerase II (RPOIILS, Croan and Ellis, 1996;Croan et al,1997), the cytochrome oxidase II gene (COII, Ibrahim and Barker, 2001;Cao et al, 2011), the glycoprotein 63 gene (gp63, Mauricio et al, 2007), cysteine protease B genes (cpb, Hide et al, 2007), the mini-exon (Sukmee et al, 2008), 7SL RNA (Zelazny et al, 2005;Guan et al, 2012), the small subunit ribosomal RNA (SSU rRNA, Guan et al, 2012), and the cytochrome B gene (cytB, LuyoAcero et al, 2004;Asato et al, 2009). Recently, Boité et al (2012) evaluated the phylogeny of Leishmania (Viannia) parasites based on multilocus sequence analysis using different housekeeping genes.…”
Section: Introductionmentioning
confidence: 99%
“…Finalmente, a mais recente leishmânia enigmática é uma espécie chinesa. Utilizando SSUrRNA, Citocromo B e ITS1 rDNA um grupo de isolados humanos e de cães posicionou-se com L. tarentolae (Cao et al, 2011;Guan et al, 2012;Yang et al, 2010Yang et al, , 2013. Além disso, recentemente foi encontrado DNA do cinetoplasto de L. tarentolae em múmias de Itacambira, Minas Gerais, Brasil, colocando em dúvida o "status" desta espécie de lagarto como não infectante para humanos (Novo et al, 2015).…”
Section: O Número De Espécies Ainda Pouco Conhecidas Descritas No Gênerounclassified